Mode of Actions of Bile Acids in Avoidance of Colorectal Cancer Development; and their Therapeutic Applications in Cancers - A Narrative Review - Kaur, Kulvinder Kochar; K. Allahbadia, Gautam Nand; Singh, Mandeep (Journal of Pharmacy and Nutrition Sciences, 2022)
Bile Acids (BAs) possess a considerably significant part in the form of emulsifiers in digestion besides absorption of dietary lipids. BAs represent amphiphilic molecules, that are primary metabolites formed from cholesterol by the aid of enzymes acting on cholesterol. Earlier BAs were believed to be tumor repressors. The tumor repressive actions of BAs are correlated with programmed cell death (PCD). Furthermore, dependent on this observation different Synthetic BAs products have been generated along with their utilization regarding induction of PCD (in the form of apoptosis, autophagy or necroptosis in variable kinds of human cancers. Thus we conducted a narrative review till August 2022. The present article might form the basis of generationof such innovative therapies even for cancers/tumors that are cisplatin resistant. With time these therapies might be used for the treatment of neurodegenerative diseases (NDD), amyotrophic sclerosis, and numerous metabolic and haematological diseases as described for use of TUDCA.